Barriers to Law Enforcement Regarding Refugees in Indonesia - Wicaksono, Anggi; Nurdin, Boy (Journal of Multidisciplinary Sustainability Asean, 2024)
Background. Indonesia serves as a transit country for refugees awaiting placement in third countries under the facilitation of the UNHCR. As Indonesia has not ratified the 1951 Refugee Convention or its 1967 Protocol, the refugees’ stay is temporary, often extending from 5 to 15 years. During this period, they are housed in government-provided shelters with the support of the International Organization for Migration (IOM). Refugees, as legal subjects, must adhere to Indonesian laws. However, the stress and uncertainty they face may lead some to commit legal violations, challenging the law enforcement process. Purpose. This study aims to explore: (1) the types of legal violations committed by refugees, (2) the factors hindering law enforcement actions against refugees, and (3) the formulation of ideal norms for justice in law enforcement regarding refugees in Indonesia. Method. This research employs a normative-empirical approach, analyzing regulations and conducting interviews with law enforcement officials to identify barriers and solutions. Results. Findings reveal that refugees often commit minor legal violations, such as unauthorized work or theft. Challenges include language barriers, limited knowledge of refugee rights among law enforcement, and lack of comprehensive policies. Conclusion. The study highlights the need for improved legal frameworks, training for law enforcement officials, and better integration of refugee management systems to ensure justice and compliance with existing laws.